Scala : applied machine learning : leverage the power of Scala and master the art of building, improving, and validating scalable machine learning and AI applications using Scala's most advanced and finest features : a course in three modules.: applied machine learning : leverage the power of Scala and master the art of building, improving, and validating scalable machine learning and AI applications using Scala's most advanced and finest features : a course in three modules. (2016) - Bugnion, Pascal; Nicolas, Patrick R; Kozlov, Alex
No abstract available